A GIS Approach to Evaluating Ecological Sensitivity for Tourism Development in Fragile Environments. A Case Study from SE Iceland - Olafsdottir, Rannveig; Runnström, Micael (Scandinavian Journal of Hospitality and Tourism, 2009)
Expansion of tourism in the northern periphery regions provides innovative resources for an economic boost to many of the peripheral communities. The northern ecosystems are however extremely vulnerable. It is therefore of vital importance for such communities to plan the growth of tourism along sustainable lines in order to secure long-term economic benefit from tourism. Geographical Information Systems (GIS) can handle multiple spatial criteria and provide a tool for the allocation of resources between conflicting demands and aid decision-makers in planning. Despite increased use of GIS in environmental planning and management, the application of GIS to tourism planning is still limited. This study aims to develop a methodology to generate a Tourism Decision Support System (TDSS) to aid planning of sustainable tourism. A GIS model was developed based on classification of identified impact factors and variables, as well as selected classification algorithms that were used to assess categories of ecological sensitivity that may aid decision makers in planning and managing sustainable tourism in sensitive areas that are facing the risk of being subjected to ecological degradation.